2015
DOI: 10.15244/pjoes/38972
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Heavy Metal Levels in Muscle and Gills of Four Benthic Fish Species from the Northeastern Mediterranean Sea

Abstract: Heavy metals are of particular concern due to their toxicity and bioaccumulation ability in aquatic ecosystems and aquatic organisms. In general, they are not biodegradable and have long biological halflives. According to the World Health Organization (WHO), heavy metals must be controlled in food sources in order to assure public safety [1]. Heavy metals are taken up and accumulated by aquatic organisms both from the surrounding medium and via food sources (deep-sea carnivorous fish in particular accumulate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The concentrations of Cd and Cr in fish were lower than in sediments [ 44 ]. These results from other studies indicated that different environments, fish species, and water quality can influence the concentration of metals in fish [ 54 ].…”
Section: Resultssupporting
confidence: 63%
“…The concentrations of Cd and Cr in fish were lower than in sediments [ 44 ]. These results from other studies indicated that different environments, fish species, and water quality can influence the concentration of metals in fish [ 54 ].…”
Section: Resultssupporting
confidence: 63%
“…According to some nutritional recommendations the PUFA/SFA ratio in human diets should be above 0.45 (Alfaia et al, 2010). A high ratio of n-3/n-6 is beneficial for reducing the risk of coronary heart diseases, and the ratio has been suggested to be a useful indicator for comparing relative nutritional values of oils (Özparlak, 2013;Olgunoglu and Artar 2016). In the present study the PUFA/SFA ratio was found to be 0.30 and 0.26 for snail meats from Adana and Sinop respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Olgunoğlu et al (2015) northeast of the Mediterranean Sea, the levels of heavy metals in muscle and gills of 4 different species of fish were studied, to then compare both quantities found. To carry out this study, samples of Merluccius merluccius, Lophius budegassa, Helicolenus dactylopterus and Chlorophtalnus agassizi, were collected at a depth between 459 and 582 m. After collecting the samples, they were rinsed with clean sea water, separated by species, stored in containers, preserved in ice and transferred to the laboratory, where both weight and size were measured.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The quantities varied between species due to their different eating and living habits, although they were in the same area. Olgunoğlu, et al (2015) concluded that the levels of heavy metals found in the fish, despite being high, were within the limits allowed by food regulations by determining that the consumption of the analyzed fish are not a risk to humans.…”
Section: Literature Reviewmentioning
confidence: 99%